HEGEMONIC DISCRIMINATION AS SEEN IN ERNEST J. GAINES’ A LESSON BEFORE DYING - Irsyadi, Achmad Naufal; Dinurriyah, Itsna Syahadatud (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2018)
The progress history of Black Africans in America remains a slice of the history of minority struggle in the world of inferiority. Racism becomes a brand topic in every sector of Blacks live in America. War and act of reformation as ways against racism are almost routinely done by Black Americans to reach their civil rights as Americans. Although the war against racism has ended, but racism atmosphere can still be felt, and it seems to have been felt by Ernest J. Gaines in his novel entitled A Lesson Before Dying. Therefore, this writing would like to analyze and describe hegemonic discrimination by White Americans. Hegemonic discrimination is a new phenomenon for Black Americans in the Southern. This theoretical foundation refers to the theory of Hegemony by Antonio Gramsci that is applied to see how discriminative hegemony is implemented smoothly and comfortably.